Low-gas-escape electromagnetic protection wave-absorbing patch and preparation method thereof

By using fluoroelastic and silicone rubber matrix combined with nanomaterials as wave absorbers in traditional wave absorbers, low-emission electromagnetic protection wave absorbing patches are prepared, which solves the problem of high gas escape rate of traditional wave absorbing materials in low-temperature vacuum and high-temperature environments, and achieves high-performance electromagnetic radiation protection effect.

CN119662024APending Publication Date: 2025-03-21NO 33 RES INST OF CHINA ELECTRONICS TECHNOOGY GRP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510035633.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional wave absorbing materials have high gas escape rate in low-temperature vacuum and high-temperature environments, resulting in pollution and performance degradation, making it difficult to meet the electromagnetic radiation protection needs in the aerospace field.

Method used

Fluoroelastomer and silicone rubber are used as substrates, combined with nanomaterials such as carbon nanotubes, graphene, carbonyl iron and ferrite as wave absorbers, and low-elastomer electromagnetic protection wave absorbing patches are prepared through molding vulcanization technology.

Benefits of technology

The preparation of low-efficiency electromagnetic protection wave-absorbing patches has been realized, which significantly reduces the interference and pollution hazards of electromagnetic radiation on equipment devices and systems, and improves the low-temperature performance of electromagnetic protection wave-absorbing materials in a simple fluoroelastic matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of wave-absorbing patches, in particular to a low-gas-escape electromagnetic protection wave-absorbing patch and a preparation method thereof. The wave-absorbing patch is prepared from the following raw materials: silicone rubber, fluororubber, hydroxyl oil, white carbon black, a vulcanizing agent and a wave-absorbing agent. In order to solve the technical problem that a traditional wave-absorbing material is high in gas escape rate, carbon nanotubes, graphene, carbonyl iron, ferrite and the like are used as wave-absorbing agents, fluororubber and silicone rubber are used as matrixes, and through the design of the mechanical performance, electromagnetic performance and environment resistance of the fluororubber and the silicone rubber, the wave-absorbing material is different from the traditional electromagnetic protection wave-absorbing material; the problem of electromagnetic radiation in the field of spaceflight is solved, and the device is especially used for occasions requiring low gas escape so as to reduce interference and pollution hazard degree of electromagnetic radiation to equipment, devices and systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of absorbing patches, and more specifically to a low outgassing electromagnetic protection absorbing patch and a preparation method thereof. Background Art

[0002] As military and civilian electronic information equipment, components and assemblies develop towards high power (high temperature resistance), miniaturization (thin film), integration, and resistance to harsh electromagnetic and space environments, the electromagnetic interference problems faced by electronic information equipment and components are increasingly becoming key issues that restrict their stable transmission and transmission of signals. High-performance electromagnetic protection absorbing materials are increasingly becoming key raw materials for solving the electromagnetic interference problems of electronic information equipment and components. When electromagnetic protection absorbing materials are applied to satellites, aircraft, spacecraft, etc., due to the high temperature environment of orbital vacuum, traditional absorbing materials may produce a large amount of outgassing pollutants, which are deposited on the functional surface that is sensitive to pollution, which may cause the performance of the optical system to decline, such as the increase in the solar absorption rate of the thermal control coating, which limits the on-orbit performance and life of the optical system. In particular, the on-orbit operating temperature of the low-temperature optical system payload is 150K or even lower. The vacuum outgassing pollutants of traditional absorbing materials will condense on the surface at this temperature, increasing the surface pollution level and accelerating the attenuation of surface performance. Regarding electromagnetic protection and absorbing materials, scientific and technological personnel have studied the microscopic morphology, structural characteristics, electromagnetic parameters and absorbing properties of absorbing materials under different processes and formulas, but there are few public reports on their use in the development of low outgassing electromagnetic protection and absorbing materials.

[0003] The present invention controls the outgassing organic pollutants of electromagnetic protection absorbing materials starting from the raw materials. Research experiments have shown that: according to the size of the vacuum sublimation value, it can be arranged as follows: natural rubber>nitrile rubber>chloroprene rubber>epimelon rubber>silicone rubber>fluororubber; according to the size of the outgassing rate value, it can be arranged as follows:epimelon rubber>silicone rubber>natural rubber>nitrile rubber>chloroprene rubber>fluororubber. Therefore, fluororubber has the smallest vacuum sublimation value and outgassing rate value. Fluororubber refers to a polymer elastomer containing fluorine atoms on the main chain and side chain carbon atoms. Due to the presence of fluorine atoms, fluororubber has excellent high temperature resistance and medium resistance, and its price is relatively low, and it has broad market prospects, but its low temperature resistance is poor. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one aspect of the present invention is to provide a low outgassing electromagnetic protection absorbing patch, the raw materials of which include silicone rubber, fluororubber, hydroxy oil, white carbon black, vulcanizing agent and absorbing agent.

[0005] Preferably, the raw material ratio is 20-30 parts of silicone rubber, 20-30 parts of fluororubber, 1-2 parts of hydroxy oil, 3-5 parts of white carbon black, 1-2 parts of vulcanizing agent and 30-50 parts of absorber.

[0006] Preferably, the absorber is a composite system of carbon nanotubes, graphene, carbonyl iron and ferrite; the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10nm-20nm, a length of 0.5μm-2μm, and a purity greater than 95%; the graphene has a flaky structure with a thickness of 0.8nm-1.2nm and a diameter of 0.5μm-5μm; the carbonyl iron is a spherical structure with a diameter of 1μm-12μm; the ferrite is Mn 0.5 Zn 0.5 Fe2O4 manganese-zinc ferrite, 200nm-600nm.

[0007] Preferably, the ratio of the carbon nanotubes, graphene, carbonyl iron and ferrite is 3-5:3-5:40-60:10-30.

[0008] Another aspect of the present invention is to provide a method for preparing a low outgassing electromagnetic protection absorbing patch, and the specific steps of the preparation method are as follows: S1. Weigh silicone rubber, fluororubber, hydroxy oil, white carbon black, vulcanizing agent and absorbent according to the proportion; S2. The weighed silicone rubber, fluororubber, hydroxy oil, white carbon black and absorbent are sequentially added to the mixing chamber of the internal mixer, and the initial mixing is closed and pressurized to obtain the initial mixing rubber. After stopping, the initial mixing rubber is poured into the mixer for mixing for the first time, and then the vulcanizing agent is added and the mixing is continued for the second time to obtain a uniformly mixed rubber; S3. The mixed rubber is opened into a film of uniform thickness; S4. Clean the mold, apply the release agent, preheat the mold, put the film in, put the mold on the heating plate, pressurize, keep warm, maintain pressure, vulcanization is completed, release the pressure, remove the mold, remove the vulcanized film, and obtain the absorbing patch product; S5. Place the absorbing patch in a vacuum oven and dry it, then cool it to room temperature, take out the absorbing patch, and shape it to obtain a low outgassing electromagnetic protection absorbing patch.

[0009] Preferably, the ratio is 20-30 parts of silicone rubber, 20-30 parts of fluororubber, 1-2 parts of hydroxy oil, 3-5 parts of white carbon black, 1-2 parts of vulcanizer and 30-50 parts of absorber; the absorber is a composite system of carbon nanotubes, graphene, carbonyl iron and ferrite, and the composite ratio is 3-5:3-5:40-60:10-30.

[0010] Preferably, the initial refining pressure in S2 is 3MPa-5MPa, the temperature is 40°C-60°C, and the time is 1 hour-2 hours.

[0011] Preferably, the first mixing time in S2 is 10 min-30 min, and the second mixing time is 10 min-20 min.

[0012] Preferably, the pressure in S4 is 10MPa-15MPa, the holding temperature is 150°C-180°C, and the holding time is 5min-10min.

[0013] Preferably, the drying temperature in S5 is 80° C.-100° C., and the drying time is 2 hours-3 hours.

[0014] The beneficial effects of the present invention are as follows: In order to solve the technical problem of high outgassing rate of traditional absorbing materials, the present invention uses carbon nanotubes, graphene, carbonyl iron, ferrite and the like as absorbers, fluororubber and silicone rubber as a matrix, and is designed through the mechanical, electromagnetic properties and environmental resistance of fluororubber and silicone rubber. It is different from traditional electromagnetic protection absorbing materials and is used to solve the electromagnetic radiation problem in the aerospace field, especially for occasions requiring low outgassing, so as to reduce the interference and pollution hazard of electromagnetic radiation to equipment components and systems.

[0015] Compared with traditional electromagnetic protection absorbing materials, the present invention adopts a new type of carbon-based carbon nanotubes and graphene absorbers, which have significant advantages of lightweight and high-performance absorbing. The new nano-carbon materials - carbon nanotubes, graphene, carbonyl iron and ferrite are compounded to adjust the dielectric constant and magnetic permeability to achieve impedance matching with free space, so that more electromagnetic waves can enter the material and be consumed, combining the advantages of the principles of electrical and magnetic loss to give full play to the structural and compositional performance advantages of various absorbers.

[0016] Compared with traditional silicone rubber-based electromagnetic protection absorbing materials, the present invention, by virtue of the low outgassing of fluororubber and the high and low temperature resistance of silicone rubber, not only maintains the original mechanical properties of traditional electromagnetic protection absorbing materials, but also has low outgassing volatility. Low outgassing electromagnetic protection absorbing materials adopt an absorber electromagnetic coupling design, which is conducive to further reducing the density of such absorbing materials and broadening the absorbing performance, which is another advantage of the present invention. The dosage of electrical absorbers carbon nanotubes and graphene can be adjusted, and the dosage of magnetic absorbers carbonyl iron and ferrite can be adjusted, and they need to be coordinated and compounded with each other.

[0017] The invention optimizes the formula design of electromagnetic protection absorbing materials based on carbon nanotubes, graphene, carbonyl iron, ferrite absorbers, fluororubber and silicone rubber matrices, synchronously designs mechanics, electromagnetics, environmental adaptability, etc., and accurately controls the dosage thereof, adjusts the components by superposition of electromagnetic synergistic losses and the dosage of absorbers, and finally forms a low-outgassing electromagnetic protection absorbing patch by mold compression vulcanization, thereby achieving high-performance absorption of electromagnetic waves, with a maximum peak value of -40 dB, a total mass loss (TML) of less than 0.2%, and a condensable volatile matter content (CVCM) of less than 0.06%, thereby realizing the preparation of low-outgassing electromagnetic protection absorbing materials, focusing on solving the problem of high outgassing rate of traditional electromagnetic protection absorbing materials, and improving the low-temperature performance of electromagnetic protection absorbing materials with a pure fluororubber matrix. The electromagnetic protection absorbing materials with both broadband characteristics and low outgassing rate developed by the invention can be used in the field of electronic information equipment systems inside satellites and spacecraft to achieve protection and absorption of electromagnetic radiation waves.

[0018] Additional aspects and advantages of the invention will become apparent from the following description, or may be learned by practice of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is a curve showing the variation of reflectivity of the sample according to the embodiment of the present invention with respect to frequency; DETAILED DESCRIPTION

[0020] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from the description. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0022] Embodiment 1 S1. Clean the mixing table and place the selected raw materials and weighing balance on the mixing table, calibrate and zero the balance, and weigh the materials according to the formula requirements (two people are required for weighing, one person weighs the materials and the other person checks and keeps records). 20 parts of silicone rubber, 30 parts of fluororubber, 2 parts of hydroxyl oil, 3 parts of white carbon black, 1 part of vulcanizing agent (double 25) and 30 parts of absorber (the compounding ratio of carbon nanotubes, graphene, carbonyl iron and ferrite is 5:5:50:10).

[0023] S2. The operator should wear work clothes and dust masks, check and clean the internal mixing equipment, start the machine according to the operating procedures of the internal mixer, open the internal mixing chamber and the cooling circulation system; add the weighed raw materials, silicone rubber, fluororubber, hydroxy oil, white carbon black and absorbent into the internal mixing chamber of the internal mixer in sequence, seal the internal mixing chamber of the internal mixer according to the operating procedures of the internal mixer, and pressurize it; start the initial mixing, control the temperature of the internal mixing chamber at 50°C, and mix for 1 hour to obtain the primary rubber; pour the primary rubber into the mixer, check and clean the internal mixing equipment; adjust the roller distance according to the operating procedures of the mixer, mix the primary rubber for 20 minutes, add the vulcanizer to the mixed rubber and mix for another 20 minutes to obtain a uniformly mixed rubber.

[0024] S3. After adjusting the mixing machine roller distance to the product thickness, the mixed rubber is rolled into films of uniform thickness.

[0025] S4. Turn on the ventilation equipment, turn on the heating switch of the flat vulcanizer according to the vulcanizer operating procedures, set the vulcanization temperature to 160°C and the vulcanization pressure to 13MPa, wear protective gloves, preheat the mold, clean the mold with cotton yarn, and apply the release agent; put the opened film into the mold; put the mold on the heating plate and pressurize it. After the pressure rises to 13MPa, keep it at 130°C and maintain the pressure (vulcanization) for 7 minutes; after the vulcanization is completed, release the pressure, take out the mold wearing protective equipment, take out the vulcanized film, and obtain the absorbing patch product.

[0026] S5. Open the vacuum oven, turn on the oven heating switch, place the absorbing patch on the material tray, put it into the vacuum oven, set the temperature to 80°C, and keep it warm for 2 hours; after completion, when the oven temperature drops to room temperature, take out the absorbing patch, arrange it into shape, and obtain a low outgassing electromagnetic protection absorbing patch.

[0027] Embodiment 2 S1. Clean the mixing table and place the selected raw materials and weighing balance on the mixing table, calibrate and zero the balance, and weigh the materials according to the formula requirements (two people are required for weighing, one for weighing and one for checking, and keep records). 30 parts of silicone rubber, 20 parts of fluororubber, 2 parts of hydroxy oil, 3 parts of white carbon black, 1 part of vulcanizing agent (double 25) and 40 parts of absorber (the compounding ratio of carbon nanotubes, graphene, carbonyl iron and ferrite is 5:5:50:10).

[0028] S2. The operator should wear work clothes and dust masks, check and clean the internal mixing equipment, start the machine according to the operating procedures of the internal mixer, open the internal mixing chamber and the cooling circulation system; add the weighed raw materials silicone rubber, fluororubber, hydroxy oil, white carbon black and absorber into the internal mixer in the internal mixing chamber in sequence, seal the internal mixing chamber of the internal mixer according to the operating procedures of the internal mixer, and pressurize it; start the initial mixing, control the temperature of the internal mixing chamber at 60°C, and mix for 1 hour to obtain the primary rubber; pour the primary rubber into the mixer, check and clean the internal mixing equipment; adjust the roller distance according to the operating procedures of the mixer, mix the primary rubber for 20 minutes, add the vulcanizer to the mixed rubber and mix for another 20 minutes to obtain a uniformly mixed rubber.

[0029] S3. After adjusting the mixing machine roller distance to the product thickness, the mixed rubber is rolled into films of uniform thickness.

[0030] S4. Turn on the ventilation equipment, turn on the heating switch of the flat vulcanizer according to the vulcanizer operating procedures, set the vulcanization temperature to 130°C, the vulcanization pressure to 13MPa, wear protective gloves, preheat the mold, clean the mold with cotton yarn, and apply the release agent; put the opened film into the mold; put the mold on the heating plate and pressurize it. After the pressure rises to 13MPa, keep it at 130°C and maintain the pressure (vulcanization) for 7 minutes; after the vulcanization is completed, release the pressure, take out the mold wearing protective equipment, take out the vulcanized film, and obtain the absorbing patch product.

[0031] S5. Open the vacuum oven, turn on the oven heating switch, place the absorbing patch on the material tray, put it into the vacuum oven, set the temperature to 80°C, and keep it warm for 2 hours; after completion, when the oven temperature drops to room temperature, take out the absorbing patch, arrange it into shape, and obtain a low outgassing electromagnetic protection absorbing patch.

[0032] Embodiment 3 S1. Clean the mixing table and place the selected raw materials and weighing balance on the mixing table, calibrate and zero the balance, and weigh the materials according to the formula requirements (two people are required to weigh the materials, one person weighs the materials and the other person checks and keeps records). 30 parts of silicone rubber, 15 parts of fluororubber, 2 parts of hydroxy oil, 2 parts of white carbon black, 1 part of vulcanizing agent (double 25) and 50 parts of absorber (the compounding ratio of carbon nanotubes, graphene, carbonyl iron and ferrite is 5:5:50:10).

[0033] S2. The operator should wear work clothes and dust masks, check and clean the internal mixing equipment, start the machine according to the operating procedures of the internal mixer, open the internal mixing chamber and the cooling circulation system; add the weighed raw materials silicone rubber, fluororubber, hydroxy oil, white carbon black and absorber into the internal mixer in the internal mixing chamber in sequence, seal the internal mixing chamber of the internal mixer according to the operating procedures of the internal mixer, and pressurize it; start the initial mixing, control the temperature of the internal mixing chamber at 60°C, and mix for 1 hour to obtain the primary rubber; pour the primary rubber into the mixer, check and clean the internal mixing equipment; adjust the roller distance according to the operating procedures of the mixer, mix the primary rubber for 20 minutes, add the vulcanizer to the mixed rubber and mix for another 20 minutes to obtain a uniformly mixed rubber.

[0034] S3. After adjusting the mixing machine roller distance to the product thickness, the mixed rubber is rolled into films of uniform thickness.

[0035] S4. Turn on the ventilation equipment, turn on the heating switch of the flat vulcanizer according to the vulcanizer operating procedures, set the vulcanization temperature to 130°C, the vulcanization pressure to 13MPa, wear protective gloves, preheat the mold, clean the mold with cotton yarn, and apply the release agent; put the opened film into the mold; put the mold on the heating plate and pressurize it. After the pressure rises to 13MPa, keep it at 130°C and maintain the pressure (vulcanization) for 7 minutes; after the vulcanization is completed, release the pressure, take out the mold wearing protective equipment, take out the vulcanized film, and obtain the absorbing patch product.

[0036] S5. Open the vacuum oven, turn on the oven heating switch, place the absorbing patch on the material tray, put it into the vacuum oven, set the temperature to 80°C, and keep it warm for 2 hours; after completion, when the oven temperature drops to room temperature, take out the absorbing patch, arrange it into shape, and obtain a low outgassing electromagnetic protection absorbing patch.

[0037] Tests of Examples 1 to 3 The test device used in the total mass loss and condensable volatile content test consists of a vacuum system, a temperature control system, a material exhaust chamber control system, and a condensable volatile deposition measurement system. Before the experiment, the samples were placed in a constant temperature and humidity environment for 24 hours, with a temperature of 23±2°C and a humidity of 50%±5%. The treated samples were evenly heated in a vacuum environment, and the total mass loss and condensable volatile content were obtained by weighing the changes in the mass of the samples and the collection plate before and after this process. The experimental results are shown in Table 1 below Table 1 The reflectivity test adopts the bow method and the test equipment is Agilent vector network analyzer. Before the test, the reflection signal of the standard conductive plate is measured first, and then the sample is placed in the position of the standard conductive plate, and the reflection signal of the sample is also tested. The reflection signal of the conductive plate and the reflection signal of the sample are compared to obtain the reflectivity of the sample.

[0038] like Figure 1The data is the curve of sample reflectivity changing with frequency, 1# is the test result of Example 1, 2# is the test result of Example 2, and 3# is the test result of Example 3. As the absorbent content increases, the minimum reflectivity moves to low frequency, and the minimum reflectivity of Example 3 reaches -45dB.

[0039] In summary, from the above results, it can be seen that the minimum reflectivity of the low outgassing electromagnetic protection absorbing patch prepared by the present invention reaches -45dB, and the total mass loss (TML) is less than 0.32%, and the condensable volatile matter content (CVCM) is less than 0.058%.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may also have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low outgassing electromagnetic protection absorbing patch, characterized in that: The raw materials of the wave-absorbing patch include silicone rubber, fluororubber, hydroxy oil, white carbon black, vulcanizing agent and wave-absorbing agent.

2. The low outgassing electromagnetic protection absorbing patch according to claim 1, characterized in that: The raw material ratio is 20-30 parts of silicone rubber, 20-30 parts of fluororubber, 1-2 parts of hydroxy oil, 3-5 parts of white carbon black, 1-2 parts of vulcanizing agent and 30-50 parts of wave absorbing agent.

3. The low outgassing electromagnetic protection absorbing patch according to claim 1, characterized in that: The wave absorber is a composite system of carbon nanotubes, graphene, carbonyl iron and ferrite; the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10nm-20nm, a length of 0.5μm-2μm and a purity greater than 95%; the graphene has a flaky structure with a thickness of 0.8nm-1.2nm and a diameter of 0.5μm-5μm; the carbonyl iron is a spherical structure with a diameter of 1μm-12μm; the ferrite is Mn 0.5 Zn 0.5 Fe2O4 manganese-zinc ferrite, 200nm-600nm.

4. The low outgassing electromagnetic protection absorbing patch according to claim 3, characterized in that: The ratio of the carbon nanotube, graphene, carbonyl iron and ferrite is 3-5:3-5:40-60:10-30.

5. The method for preparing a low outgassing electromagnetic protection absorbing patch according to claim 1, characterized in that: The specific steps of the preparation method are as follows: S1. Weigh silicone rubber, fluororubber, hydroxy oil, white carbon black, vulcanizing agent and absorbent according to the proportion; S2. The weighed silicone rubber, fluororubber, hydroxy oil, white carbon black and absorbent are sequentially added to the mixing chamber of the internal mixer, and the initial mixing is closed and pressurized to obtain the initial mixing rubber. After stopping, the initial mixing rubber is poured into the mixer for mixing for the first time, and then the vulcanizing agent is added and the mixing is continued for the second time to obtain a uniformly mixed rubber; S3. The mixed rubber is opened into a film of uniform thickness; S4. Clean the mold, apply the release agent, preheat the mold, put the film in, put the mold on the heating plate, pressurize, keep warm, maintain pressure, vulcanization is completed, release the pressure, remove the mold, remove the vulcanized film, and obtain the absorbing patch product; S5. Place the absorbing patch in a vacuum oven and dry it, then cool it to room temperature, take out the absorbing patch, and shape it to obtain a low outgassing electromagnetic protection absorbing patch.

6. The method for preparing a low outgassing electromagnetic protection absorbing patch according to claim 5, characterized in that: The ratio is 20-30 parts of silicone rubber, 20-30 parts of fluororubber, 1-2 parts of hydroxy oil, 3-5 parts of white carbon black, 1-2 parts of vulcanizing agent and 30-50 parts of absorber; the absorber is a composite system of carbon nanotubes, graphene, carbonyl iron and ferrite, and the composite ratio is 3-5:3-5:40-60:10-30.

7. The method for preparing a low outgassing electromagnetic protection absorbing patch according to claim 5, characterized in that: The initial refining pressure in S2 is 3MPa-5MPa, the temperature is 40°C-60°C, and the time is 1 hour-2 hours.

8. The method for preparing a low outgassing electromagnetic protection absorbing patch according to claim 5, characterized in that: The first mixing time in S2 is 10 min-30 min, and the second mixing time is 10 min-20 min.

9. The method for preparing a low outgassing electromagnetic protection absorbing patch according to claim 5, characterized in that: The pressure in S4 is 10MPa-15MPa, the insulation temperature is 150°C-180°C, and the pressure holding time is 5min-10min.

10. The method for preparing a low outgassing electromagnetic protection absorbing patch according to claim 5, characterized in that: The drying temperature in S5 is 80° C.-100° C., and the drying time is 2 hours-3 hours.

Citation Information

Patent Citations

  • Blend of fluorubber and silastic, and preparation thereof

    CN101412835A

  • Silicone rubber-based wave-absorbing patch and preparation method thereof

    CN111040453A

  • Corrosion-resistant waveguide heat-conducting silicone rubber composite gasket and preparation method thereof

    CN114957995A

  • High-strength wave-absorbing silica gel sheet and preparation method thereof

    CN118791875A